Fiendish deeds - Bracegirdle, P. J. (Bracegirdle, P. J. Joy of Spooking, 2008)
As eleven-year-old Joy Wells, proud resident of the nearly-abandoned town of Spooking, tries to stop construction of a water park in a bog she believes is home to a monster and the setting of her favorite horror story, a man with his own mysterious connection to Spooking will do anything to stop her.